Health, quality of life, and wellbeing of older slum dwellers in sub-Saharan Africa: A scoping review. Issue 12 (2nd December 2021) - Alaazi, Dominic A.; Menon, Devidas; Stafinski, Tania
ABSTRACT: A growing population of older adults resides in sub-Saharan Africa's urban slums. Although environmental conditions in slums are adversarial, there is limited knowledge on the wellbeing of older adults residing in these settings. This review sought to understand the scope, extent, and nature of current research on the health and wellbeing of older slum dwellers in sub-Saharan Africa. We searched 8 bibliographic databases for studies examining the health and wellbeing of older slum dwellers in the region. We also completed a grey literature search. The literature search together yielded 3, 388 records, of which we selected 25 for review following a rigorous screening process. The included studies covered a variety of health issues of concern to older slum dwellers: (1) disease and injury prevalence; (2) self-assessed health and quality of life status; (3) physical/mental health impairment and disability; (4) healthcare access and utilisation; and (5) sociodemographic disparities in health and wellbeing. The gaps in this literature include a regional bias in research efforts, near absence of non-slum control samples, and limited research on the health impacts of the built environment of slums. Suggestions for future research are presented.